PERAN PONDOK PESANTREN SUNAN DRAJAT DALAM PEMBERDAYAAN EKONOMI - Maulia Rahmatika; Sunan Fanani (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
Pesantren are Islamic educational institutions that participate in the empowerment of the community's economy through their efforts. One of the pesantren famous for its wealth is Pesantren Sunan Drajat Lamongan, East Java. The purpose of this study was to knowing about the role of Pesantren Sunan Drajat in economic empowerment. The research method was descriptive qualitative with case study design. The research data collected by interview, direct observation, and documentation. The collected data is validated by means of source and technique triangulation. The role of economic empowerment built in this study refers to the CIPP evaluation model. Based on the results of the analysis show that the economic empowerment of the PesantrenSunanDrajat which is renewed through CIPP approved to be able to educate the students' mentality and expertise, and improve the standart living of society. There are also pesantren activities that lead to indirect empowerment, which can help the economic welfare of santri and the society.Keyword: Economic Empowerment, Pesantren, CIPP Evaluation Model